Living conditions, social exclusion and mental well-being - Layte, Richard; Maître, Bertrand; Whelan, Christopher T. (Luxembourg, 2010)
"Over the past two decades, the concept of social exclusion has increasingly replaced the concept of poverty within the EU policy discussion on social vulnerability and disadvantage. It has been shown that unequal access to the labour market and poor living conditions negatively affect social participation and social contact, which in turn impact on the quality of life of Europe’s citizens and lead to a sense of social exclusion. The second European Quality of Life Survey (EQLS), conducted by Eurofound in 2007, offers a wide-ranging view of the diverse social realities in Europe today. This report looks at the relationships between living conditions, social exclusion and mental well-being."